On Wood–Water Interactions in the Over-Hygroscopic Moisture Range—Mechanisms, Methods, and Influence of Wood Modification - Maria Fredriksson (Forests, 2019)
Wood is a hygroscopic material that absorbs and desorbs water to equilibrate to the ambient climate. Within material science, the moisture range from 0 to about 95−98% relative humidity is generally called the hygroscopic moisture range, while the exceeding moisture range is called the over-hygroscopic moisture range. For wood, the dominating mechanisms of moisture sorption are different in these two moisture ranges; in the hygroscopic range, water is primarily bound by hydrogen bonding in cell walls, and, in the over-hygroscopic range, water uptake mainly occurs via capillary condensation outside cell walls in macro voids such as cell lumina and pit chambers. Since large volumes of water can be taken up here, the moisture content in the over-hygroscopic range increases extensively in a very narrow relative humidity range. The over-hygroscopic range is particularly relevant for durability applications since fungal degradation occurs primarily in this moisture range. This review describes the mechanisms behind moisture sorption in the over-hygroscopic moisture range, methods that can be used to study the interactions between wood and water at these high humidity levels, and the current state of knowledge on interactions between modified wood and water. A lack of studies on interactions between modified wood and water in the over-hygroscopic range was identified, and the possibility of combining different methods to acquire information on amount, state, and location of water in modified wood at several well-defined high moisture states was pointed out. Since water potential is an important parameter for fungal growth, such studies could possibly give important clues concerning the mechanisms behind the increased resistance to degradation obtained by wood modification.